Evaluation of Eating Habits and Quality of Life in Postbariatric Surgery Patients and Their Family Members: A Case-Control Study - Carla Ibrahim; Joane Matta; Kàtia Lurbe i Puerto; Yonna Sacre (Journal of Nutrition and Metabolism)
Background. Obesity is a major health problem worldwide. Today, bariatric surgery is considered as the last option and most effective treatment for severe obesity (BMI ≥40 kg/m2 or BMI ≥35 kg/m2 with metabolic conditions). Aims. We aimed to evaluate the medium-term effect (>36 months) of bariatric surgery and assess postbariatric nutritional and lifestyle management among Lebanese patients who underwent bariatric surgeries in Jbeil and Keserwan hospitals. Methods. This study is a quantitative case-control study. The case group includes a couple of patients who have undergone sleeve or bypass surgery 6 months ago and above, along with the main family caregivers. The control group constitutes a couple of obese patients with BMI ≥30 kg/m2 who did not proceed to any surgical intervention with their main caregivers. The final samples consisted of 53 cases and caregivers and 50 controls and caregivers. The assessment was made by an online questionnaire. Results. Compared to obese patients, bariatric patients were less likely to have high energy intake (54% versus 34%, P value 0.012). Moreover, 35.8% of the caregivers of bariatric patients had a low physical activity level compared to those of the control group who had a lower level (70%). In addition, cases’ main caregivers (75.5%) had much higher quality of life compared to the cases (56.6%), and also, higher quality of life was seen among the case’s main caregivers (75%) compared to the controls (72%). Conclusion. In Jbeil and Keserwan regions of Lebanon, there is a lack of postbariatric nutritional and lifestyle management leading to less desirable outcomes in the medium to long term. A set of recommendations are developed based on this study.